THEORY AND PRACTICE OF RUSSIAN PUBLIC DEBT MANAGEMENT - O. A. Revzon (Вестник университета)
The article considers the approaches to public debt management in Russia, describes the time requirements for the use of various tools. The paper evaluates the dynamics of changes in public debt and its transformation, which consists in the transition from external to internal borrowing. The author denotes problems in the field of underfunding of budget expenditures in connection with the coronavirus pandemic. The study considers all known theories of public debt management and presents the mechanism of their implementation and their impact on the state of public finances. The author makes a summary of the necessary approaches and solutions in the field of borrowing and debt servicing. The paper also presents the direction of changes in the legislation in the field of setting service limits and the total amount of borrowing.